PERSEPSI MASYARAKAT TENTANG KUALITAS PELAYANAN KESEHATAN DI RUMAH SAKIT UMUM DAERAH KOTA KOTAMOBAGU PROVINSI SULAWESI UTARA - Tawil, Mohamad Yusuf; Ruru, Joorie Marhaen; Londa, Very Yohanis (Sam Ratulangi University, 2017)
Liquid health services every effort held alone or together in an organizationto maintain and promote health, prevent and cure disease and restore the health ofindividuals, families, groups or communities. Looked at that hospital patientsshould be more capable in providing health services in the quest of healing andrestoration of quality, fast on the outside top of the complaints as well as theprovision of health services.This research uses qualitative research methods, descriptive, the number ofinformants will be interviewed in this study amounted to 8 (eight) theinformant; 1 person head of sub-division of The HOSPITALS of thecity of Kotamobagu, 1 Staff Officer, 6 people of the communitywho are receiving services (patient). Data collection techniques are in use;interview techniques, techniques of observation, and data collection techniques,with documents. The data analysis techniques in use; reduction of data,data presentation, and conclusion / verification of withdrawal.Keywords: Public Perception, Quality of Service